Beyond the Meme Development and Structure in Cultural Evolution - Love, Alan C.; Wimsatt, William (Minnesota Studies in the Philosophy of Science, 2019)
Interdisciplinary perspectives on cultural evolution that reject meme theory in favor of a complex understanding of dynamic change over time How do cultures change? In recent decades, the concept of the meme, posited as a basic unit of culture analogous to the gene, has been central to debates about cultural transformation. Despite the appeal of meme theory, its simplification of complex interactions and other inadequacies as an explanatory framework raise more questions about cultural evolution than it answers. In Beyond the Meme, William C. Wimsatt and Alan C. Love assemble interdisciplinary perspectives on cultural evolution, providing a nuanced understanding of it as a process in which dynamic structures interact on different scales of size and time. By focusing on the full range of evolutionary processes across distinct contexts, from rice farming to scientific reasoning, this volume demonstrates how a thick understanding of change in culture emerges from multiple disciplinary vantage points, each of which is required to understand cultural evolution in all its complexity. The editors provide an extensive introductory essay to contextualize the volume, and Wimsatt contributes a separate chapter that systematically organizes the conceptual geography of cultural processes and phenomena. Any adequate account of the transmission, elaboration, and evolution of culture must, this volume argues, recognize the central roles that cognitive and social development play in cultural change and the complex interplay of technological, organizational, and institutional structures needed to enable and coordinate these processes. Contributors: Marshall Abrams, U of Alabama at Birmingham; Claes Andersson, Chalmers U of Technology; Mark A. Bedau, Reed College; James A. Evans, U of Chicago; Jacob G. Foster, U of California, Los Angeles; Michel Janssen, U of Minnesota; Sabina Leonelli, U of Exeter; Massimo Maiocchi, U of Chicago; Joseph D. Martin, U of Cambridge; Salikoko S. Mufwene, U of Chicago; Nancy J. Nersessian, Georgia Institute of Technology and Harvard U; Paul E. Smaldino, U of California, Merced; Anton Törnberg, U of Gothenburg; Petter Törnberg, U of Amsterdam; Gilbert B. Tostevin, U of Minnesota.